1992
DOI: 10.1113/jphysiol.1992.sp019152
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic reticulum buffering of myoplasmic calcium in bovine coronary artery smooth muscle.

Abstract: SUMMARY1. We tested the hypothesis that the sarcoplasmic reticulum (SR) buffers (attenuates) the increase in averaged myoplasmic free [Ca2+] (Caim)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…B (Jelicks & Gupta, 1990;Okada, Ishikawa & Saito, 1992;Sturek, Kunda & Hu, 1992;Quamme, Dai & Rabkin, 1993 (Golowasch et al 1986;Trieschmann & Isenberg, 1989;Zhang et al 1995).…”
Section: Methodsmentioning
confidence: 99%
“…B (Jelicks & Gupta, 1990;Okada, Ishikawa & Saito, 1992;Sturek, Kunda & Hu, 1992;Quamme, Dai & Rabkin, 1993 (Golowasch et al 1986;Trieschmann & Isenberg, 1989;Zhang et al 1995).…”
Section: Methodsmentioning
confidence: 99%
“…The extent of control that the sarcoplasmic reticulum (SR) might have in regulating intracellular Ca2l in vascular smooth muscle is an area of much discussion (Allen & Seidel, 1986). Sturek et al (Sturek et al 1992) demonstrated that the SR in vascular smooth muscle attenuates the increase in myoplasmic free Ca2+ (Caim) resulting from Ca21 influx. This being the case, when the SR is Ca2+-loaded it can no longer sequester the continuing influx of Ca2+ into the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, three distinct models have beefi proposed to describe the regulation of intracellular Ca2+ by the endoplasmic/sarcoplasmic reticulum (see companion paper (Sturek, Kunda & Hu, 1992) for details). The extent of control that the sarcoplasmic reticulum (SR) might have in regulating intracellular Ca2l in vascular smooth muscle is an area of much discussion (Allen & Seidel, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that in microsomes from vas cular smooth muscles, the Ca2+-uptake depended on the free Ca 2+ concentration outside the vesicles (26). Sturek et al (23) showed that when [Ca 2+1 i was higher, the sub sequent caffeine-induced [Ca 2+] i transient was proportion ally larger, indicating a greater Ca 2+ uptake at higher cytoplasmic Ca2+. Therefore, an elevation of [Ca 2+] i due to increased Ca 2+ influx by PE may be associated with the enhancement of Ca 2+ uptake into the SR in the presence of PE.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the functions of the SR in smooth muscles, the Ca 2+ pump promotes the uptake of Ca2+ influxed from the extracellular space; thereby, the SR works to reduce [Ca 2+] i (22,23). In such a situation, an interven tion to inhibit the SR Ca 2+ pump would increase [Ca 2+] i (24).…”
Section: Discussionmentioning
confidence: 99%